PICTURE WORDS INDUCTIVE MODEL FOR YOUNG LEARNER IN IMPROVING ENGLISH VOCABULARY FOR INDONESIAN STUDENTS AT SD SWASTA PELANGI MEDAN - Ernita Daulay (VISION, 2020)
The Picture word inductive is an inquiry-oriented language arts strategy that uses pictures containing familiar objects and actions to elicit words from children's listening and speaking vocabularies. This strategy leads the students to identify each object in a picture that they will describe. The aim of this study was to find out the effectiveness of Picture Word Inductive Model in improvement vocabulary skills‟ for Indonesian students at SD Swasta Pelangi Medan. The population of this research is the Second year students at SD Swasta Pelangi. The number of sample is 28 students selected by using cluster random sampling technique. Based on the result of this research, the writer suggest that Picture Word Inductive Model may be used as alternative media in teaching vocabulary, in order that the students can more understand and interested in learning activity especially in learning of English.